Marketing digital y posicionamiento de la empresa restobar Ajidulce, Iquitos 2023 - Rimachi Noriega, Viviana (2024)
The aim of this thesis is to determine the relationship between digital marketing and the positioning of Restobar Ajidulce in Iquitos in 2023. A quantitative approach was employed using the SPSS program to analyze numerical data. Key results reveal high reliability in both variables, with 70% of respondents placing digital marketing and positioning at medium levels. The Pearson correlation was significant (0.560), indicating a positive connection: improvements in digital marketing coincide with enhancements in positioning, and vice versa. Statistical significance supports the acceptance of the hypothesis. Specific conclusions show that 70% perceive digital marketing as "Medium," refuting the hypothesis. Regarding positioning, 72% classify it as "Medium," also refuting the hypothesis. Overall, a positive and significant correlation between digital marketing and the company's positioning is confirmed. The general hypothesis is accepted, emphasizing the need for continuous improvement in both areas.